Identification of Salmonella enterica serovar Kentucky genes involved in attachment to chicken skin. Issue 1 (December 2016) - Salehi, Sanaz; Howe, Kevin; Brooks, John; Lawrence, Mark; Bailey, R.; Karsi, Attila
Abstract Background Regardless of sanitation practices implemented to reduceSalmonella prevalence in poultry processing plants, the problem continues to be an issue. To gain an understanding of the attachment mechanism ofSalmonella to broiler skin, a bioluminescent-based mutant screening assay was used. A random mutant library of a field-isolated bioluminescent strain ofSalmonella enterica serovar Kentucky was constructed. Mutants' attachment to chicken skin was assessed in 96-well plates containing uniform 6 mm diameter pieces of circular chicken skin. After washing steps, mutants with reduced attachment were selected based on reduced bioluminescence, and transposon insertion sites were identified. Results Attachment attenuation was detected in transposon mutants with insertion in genes encoding flagella biosynthesis, lipopolysaccharide core biosynthesis protein, tryptophan biosynthesis, amino acid catabolism pathway, shikimate pathway, tricarboxylic acid (TCA) cycle, conjugative transfer system, multidrug resistant protein, and ATP-binding cassette (ABC) transporter system. In particular, mutations inS . Kentucky flagellar biosynthesis genes (flgA, flgC, flgK, flhB, andflgJ ) led to the poorest attachment of the bacterium to skin. Conclusions The current study indicates that attachment ofSalmonella to broiler skin is a multifactorial process, in which flagella play an important role.